GUS BAHA, SANTRI GAYENG, AND THE RISE OF TRADITIONALIST PREACHERS ON SOCIAL MEDIA (JOURNAL OF INDONESIAN ISLAM, 2022)
This research discusses the efforts of the old religious authority in Indonesia, particularly NU activists and preachers, to maintain its values amidst the substantial exposure of new online preachers. This study employs qualitative methods by observing da’wah on social media platforms: Instagram, Facebook, Twitter, and YouTube. The sample of this research is the da’wah of KH. Bahauddin Nursalim (Gus Baha) through Santri Gayeng’s social media accounts. This research argues that the online da’wah of NU, specifically Gus Baha and Santri Gayeng, is adequate and effective to compete with online Islamist activities, such as those from former HTI members. The success of Santri Gayeng is attributed to its strategy to implement da’wah 2.0, which maximizes visual aesthetics, communication skills, and marketing tactics, besides the use of Indonesian subtitles. These factors have attracted audiences comprising Nahdlatul Ulama members as well as former jihadists to Gus Baha’s house to listen to and broadcast his lectures online. The response of traditionalist Islam groups through Santri Gayeng has two meanings; namely, it marks the engagement of NU followers in online da’wah interactions and enhances the characteristics of related moderate groups in Indonesia.